La salud en el plan nacional de desarrollo: sin cambios para construir la paz (1999)
ABSTRACT: The 1999-2002 National Development Plan issued through the Law 508 of 1999 proposes as health policy for this period, to go deeply into the functioning mechanisms of the current welfare system. No strategies are suggested to overcome very crucial problems such as, the exclusion from health services suffered by a huge portion of the community, the high costs caused by intermediaries, the crisis in the public hospitals, the reduction in health oriented programs and the fragmentation of the community’s participation. The health crisis that Colombian are experiencing now, requires structural goal changes and strategies of social and economic development in order to avoid a deeper deterioration of the public health situation.